Optimizing Millennial Performance: The Role of Talent Management, Work-Life Balance, and Stress Management - Lutfillahi Latief; Dimas Prasetyo; Febrianur Ibnu Fitroh Sukono Putra (BUSMI : Journal of Business and Management Innovations, 2025)
The purpose of this study is to find out how talent management influences employee performance, the effect of work-life balance on employee performance, and the effect of work stress on employees. This research was conducted on 58 millennial- generation employees at Point Coffee in Semarang City. Testing the instrument in the study was carried out by testing the validity and reliability tests. The method used in this research is multiple linear regression analysis with the help of SPSS 25. The results of the study show that talent management, work-life balance, and work stress have a positive and significant effect on employee performance. The results of this study are expected to provide information and contribute to the development of knowledge related to the influence of talent management, work-life balance, and work stress on employee performance. The results of this research are also expected to assist in the teaching and learning process and to apply knowledge, especially human resource management related to talent management, work-life balance, work stress, and employee performance.